Small Firms and Domestic Bank Dependence in Europe's Great Recession - Mathias Hoffmann; Egor Maslov; Bent E. Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2019)
Small businesses (SMEs) depend on banks for credit. We show that the severity of the Eurozone crisis was worse in countries where firms borrowed more from domestic banks (“domestic bank dependence”) than in countries where firms borrowed more from international banks. Eurozone banking integration in the years 2000–2008 mainly involved cross-border lending between banks while foreign banks' lending to the real sector stayed flat. Hence, SMEs remained dependent on domestic banks and were vulnerable to global banking shocks. We confirm, using a calibrated quantitative model, that domestic bank dependence makes sectors and countries with many SMEs vulnerable to global banking shocks.
Keywords: F30; F36; F40; F45; 330; small and medium enterprises; SME access to finance; banking integration; domestic bank dependence; international transmission; Eurozone crisis